Preparation methods of 3D cage-shaped solid electrolyte composite microspheres, solid electrolyte hydrogel and diaphragm, and secondary battery
By coating 3D cage-shaped solid electrolyte composite microspheres and solid electrolyte hydrogel on the lithium-ion battery separator, the electrolyte wetting and temperature stability of the separator is solved, and the energy density and cycle stability of the battery are improved, ensuring that Safety performance at high temperatures.
Patent Information
- Application Number
- CN202411585700.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2024-12-24
AI Technical Summary
The separator of existing lithium-ion batteries has problems such as poor electrolyte wetting and liquid retention, unstable temperature, and inability to effectively inhibit polysulfide shuttle, which limits the high energy density and cycle stability of the battery.
The composite microspheres were prepared by LBL treatment and sintering technology using 3D cage-shaped solid electrolyte composite microspheres and solid electrolyte hydrogels, and coated on the separator to improve ion conductivity, thermal stability and mechanical strength.
It improves the overall performance and safety of the battery, enhances the migration ability of lithium ions and the cycle stability of the battery, reduces the occurrence of side reactions, and is suitable for high temperature conditions.
Smart Images

Figure BDA0005124238060000261 
Figure HDA0005124238120000011 
Figure HDA0005124238120000012
Abstract
Description
Technical Field
[0001] The present invention relates to the field of battery materials, and in particular to a preparation method of a 3D cage-shaped solid electrolyte composite microsphere, a solid electrolyte hydrogel, a diaphragm, and a secondary battery. Background Art
[0002] Lithium-ion batteries have been widely used in energy storage grids, portable electronic products, electric vehicles and other fields. However, the continuous expansion of the electric vehicle market requires high energy density and safe lithium secondary battery systems. The development of new battery systems has brought a series of scientific problems, such as the loss of irreversible capacity of the first cycle of lithium-ion batteries due to the formation of solid electrolyte interfaces, the uneven deposition of lithium ions on the lithium metal negative electrode leading to dendrite growth, and the shuttle effect caused by the dissolution of sulfur positive electrodes in lithium-sulfur batteries. These problems restrict the commercial application of high energy density batteries. As one of the key components of lithium secondary batteries, the main function of the separator is to provide ion transmission channels, isolate the positive and negative electrodes, and prevent short circuits inside the battery.
[0003] Although the current mainstream polyolefin separators have suitable pore structures, electrochemical stability, and low production costs, they still have some shortcomings that cannot be ignored. Specifically, they are manifested in three aspects: (1) The electrolyte wettability and liquid retention are poor, and leakage is prone to occur, affecting the electrochemical performance and safety performance of the battery; (2) The polyolefin separator obtained by stretching orientation is dimensionally unstable when the temperature rises, and shrinks, affecting the safety of the battery; (3) It cannot effectively inhibit the shuttle of polysulfides, affecting the cycle life of lithium-sulfur batteries. As an intermediate layer, the separator is in direct contact with the positive and negative electrodes, and has its unique advantages in solving scientific problems existing in the electrodes. Therefore, it is of great theoretical significance and application value to develop a functional separator that can improve the battery energy density, cycle stability, and safety performance at high temperatures. Summary of the invention
[0004] In view of this, the present invention provides a 3D cage-shaped solid electrolyte composite microsphere, a solid electrolyte hydrogel, a preparation method of a separator, and a secondary battery. The 3D cage-shaped solid electrolyte composite microsphere provided by the present invention can improve the ion conductivity, thermal stability and mechanical strength of the battery separator, thereby improving the overall performance and safety of the battery.
[0005] The present invention provides a method for preparing 3D cage-shaped solid electrolyte composite microspheres, comprising the following steps:
[0006] A) grinding the inorganic solid electrolyte to obtain a ground LATP;
[0007] in,
[0008] The inorganic solid electrolyte is a NASICON type solid electrolyte Li1+x Al x Ti 2-x (PO4)3, 0≤x<1;
[0009] B) subjecting the ground LATP obtained in step A) to LBL treatment to obtain modified LATP;
[0010] in,
[0011] In the LBL process, the cationic polymer is deposited first and then the anionic polymer;
[0012] The cationic polymer is at least one of PLL, PDDA, PPy and PEI;
[0013] The anionic polymer is at least one of PSS, PEO, PVDF and PAAS;
[0014] C) dispersing yeast powder in acid solution to obtain yeast powder dispersion;
[0015] D) mixing the yeast powder dispersion obtained in step C), the modified LATP obtained in step B) and a surfactant, and heating them for reaction to obtain a LATP-yeast-LATP complex;
[0016] E) sintering the LATP-yeast-LATP complex obtained in step D) to obtain 3D cage-shaped solid electrolyte composite microspheres;
[0017] There is no order restriction for step B) and step C).
[0018] Preferably, in step C):
[0019] The acid solution is HCl solution;
[0020] The pH of the yeast powder dispersion is 2 to 3;
[0021] In step D), the heating reaction temperature is 80-150° C. and the time is 3-7 hours.
[0022] Preferably, in step D):
[0023] The amount of yeast powder in the yeast powder dispersion is 20% to 50% of the mass of the modified LATP;
[0024] The amount of the surfactant is 5% to 10% of the mass of the modified LATP;
[0025] The surfactant is at least one of polyvinyl alcohol, sodium carboxymethyl cellulose and polyvinyl pyrrolidone.
[0026] Preferably, in step E), the sintering treatment is performed at a temperature of 500 to 700° C. for 2 to 6 hours.
[0027] The present invention also provides a 3D cage-shaped solid electrolyte composite microsphere prepared by the preparation method described in the above technical solution.
[0028] The present invention also provides a method for preparing a solid electrolyte hydrogel, comprising the following steps:
[0029] S1, mixing a hydrophilic ionic monomer, an acrylate compound and a solvent, and irradiating the mixture to obtain a polymer carrier;
[0030] S2, mixing the mother ball, the solvent and the polymer carrier obtained in step S1 to obtain a solid electrolyte hydrogel;
[0031] Wherein, the mother ball is the 3D cage-shaped solid electrolyte composite microsphere as described in claim 5.
[0032] Preferably, in step S1:
[0033] The hydrophilic ionic monomer is at least one of methacryloyloxyethyl trimethyl ammonium chloride, dimethyl diallyl ammonium chloride, acrylic acid, methacrylic acid, sodium p-styrene sulfonate and carboxylic acid betaine;
[0034] The acrylate compound is at least one of diethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, non-ethylene glycol dimethacrylate and tetradecaethylene glycol dimethacrylate;
[0035] The irradiation is carried out using 60 γ-ray irradiation of Co;
[0036] The irradiation temperature is -80 to -50°C;
[0037] The irradiation has a dose rate of 10 to 15 kGy / h and a duration of 1 to 5 hours.
[0038] The present invention also provides a solid electrolyte hydrogel prepared by the preparation method described in the above technical solution.
[0039] The present invention also provides a method for preparing a diaphragm, comprising the following steps:
[0040] coating the hydrogel on the surface of the basement membrane and drying it to obtain a separator;
[0041] Wherein, the hydrogel is the solid electrolyte hydrogel described in the above technical solution.
[0042] The present invention also provides a secondary battery, wherein the diaphragm is a diaphragm prepared by the preparation method described in the above technical solution.
[0043] The present invention provides a new type of 3D cage-shaped solid electrolyte composite microspheres, which not only show excellent ionic conductivity and excellent interface compatibility, but also can effectively inhibit volume expansion, thereby ensuring long-term stability in the application of solid electrolyte structures. When the solid electrolyte microspheres with this special structure are used to coat the diaphragm and applied in lithium batteries, they can provide abundant ion transmission channels, promote the rapid migration of lithium ions, and enhance the adsorption capacity of lithium ions, so that the battery can store more energy at the same volume. This is difficult to achieve in many other solid electrolyte applications. The significant difference from other diaphragm coatings is that the unique cage structure provides additional mechanical support for the diaphragm, enhances the mechanical strength of the diaphragm, helps to maintain the stability of the battery structure, and reduces the structural damage caused by volume changes. Moreover, the surface of the diaphragm is rich in LATP materials and carbon balls, has excellent thermal stability, helps to maintain battery performance and safety under high temperature conditions, while reducing the occurrence of side reactions and improving the cycle stability of the battery. The composite solid electrolyte gel-coated diaphragm prepared by the present invention has a very low interfacial impedance on its surface, enhances the wettability with materials such as electrolytes, and helps to improve the charging and discharging efficiency of the battery, thereby meeting the urgent needs of modern electronic devices and electric vehicles for high energy density batteries. Therefore, the composite solid electrolyte gel-coated diaphragm technology of the present invention not only improves the performance and safety of the battery, but also provides new possibilities for the future development of battery technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0045] Figure 1 This is a microscopic morphology of the 3D cage-shaped solid electrolyte composite microsphere sample prepared in Example 1;
[0046] Figure 2 The microscopic morphology of the solid electrolyte hydrogel coated on the separator in Example 1. DETAILED DESCRIPTION
[0047] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.
[0048] In this article, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0049] As used herein, the term "and / or" includes any and all combinations of one or more of the associated listed items.
[0050] Herein, when it comes to numerical ranges, unless otherwise specified, the numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0051] In this article, when referring to the unit of a data range, if there is a unit only after the right endpoint, it means that the units of the left and right endpoints are the same. For example, 0.3-0.7mm means that the units of the left endpoint "0.3" and the right endpoint "0.7" are both mm.
[0052] Only some numerical ranges are specifically disclosed herein. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, and likewise any upper limit can be combined with any other upper limit to form an unspecified range. In addition, each separately disclosed point or single value can itself be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an unspecified range.
[0053] The present invention provides a method for preparing 3D cage-shaped solid electrolyte composite microspheres, comprising the following steps:
[0054] A) grinding the inorganic solid electrolyte to obtain a ground LATP;
[0055] in,
[0056] The inorganic solid electrolyte is a NASICON type solid electrolyte Li 1+x Al x Ti 2-x (PO4)3, 0≤x<1;
[0057] B) subjecting the ground LATP obtained in step A) to LBL treatment to obtain modified LATP;
[0058] in,
[0059] In the LBL process, the cationic polymer is deposited first and then the anionic polymer;
[0060] The cationic polymer is at least one of PLL, PDDA, PPy and PEI;
[0061] The anionic polymer is at least one of PSS, PEO, PVDF and PAAS;
[0062] C) dispersing yeast powder in acid solution to obtain yeast powder dispersion;
[0063] D) mixing the yeast powder dispersion obtained in step C), the modified LATP obtained in step B) and a surfactant, and heating them for reaction to obtain a LATP-yeast-LATP complex;
[0064] E) sintering the LATP-yeast-LATP complex obtained in step D) to obtain 3D cage-shaped solid electrolyte composite microspheres;
[0065] There is no order restriction for step B) and step C).
[0066] [About Step A]:
[0067] A) The inorganic solid electrolyte is ground to obtain ground LATP.
[0068] In the present invention, the inorganic solid electrolyte is a NASICON type solid electrolyte Li 1+x Al x Ti 2-x (PO4)3, 0≤x<1, x can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9; in some embodiments of the present invention, the inorganic solid electrolyte is Li 1.1 Al 0.1 Ti 1.9 (PO4)3、Li 1.2 Al 0.2 Ti 1.8 (PO4)3、Li 1.3 Al 0.3 Ti 1.7 (PO4)3、Li 1.4 Al 0.4 Ti 1.6 (PO4)3、Li 1.5 Al 0.5 Ti 1.5 (PO4)3、Li 1.6 Al 0.6 Ti 1.4 (PO4)3、Li 1.9 Al 0.9 Ti 1.1 (PO4)3.1+x Al x Ti 2-x (PO4)3 is lithium aluminum titanium phosphate, abbreviated as LATP, which is an inorganic solid electrolyte with high ionic conductivity. 1+x Al x Ti 2-x The source of (PO4)3 is not particularly limited and can be a commercial product or one prepared according to a preparation method known in the art.
[0069] In the present invention, the grinding method is preferably sand grinding. The equipment used for sand grinding is a sand mill.
[0070] The grinding medium used in the grinding is preferably at least one of water, anhydrous ethanol and N-methylpyrrolidone (NMP). The water is preferably deionized water. The mass ratio of the inorganic solid electrolyte to the grinding medium is preferably 1: (2-4), specifically 1: 1, 1: 2, 1: 3, and more preferably 1: 3.
[0071] The grinding balls used in the grinding are preferably zirconium oxide balls. The diameter of the grinding balls is preferably 0.3-0.7 mm, specifically 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm.
[0072] The grinding speed is preferably 500-2000r / min, specifically 500r / min, 600r / min, 700r / min, 800r / min, 900r / min, 1000r / min, 1100r / min, 1200r / min, 1300r / min, 1400r / min, 1500r / min, 1600r / min, 1700r / min, 1800r / min, 1900r / min, 2000r / min. The grinding time is preferably 2-12h, specifically 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h.
[0073] The present invention grinds the inorganic solid electrolyte LATP into nanoscale slurry by grinding, and then dries to obtain the ground LATP. The D50 particle size of the nanoscale slurry is preferably 100-400nm, specifically 100nm, 107nm, 110nm, 120nm, 130nm, 140nm, 142nm, 150nm, 160nm, 168nm, 170nm, 180nm, 187nm, 190nm, 200nm, 243nm, 251nm, 300nm, 327nm, 350nm, 353nm, 391nm, 392nm, 400nm.
[0074] [About step B]:
[0075] B) subjecting the ground LATP obtained in step A) to LBL treatment to obtain modified LATP.
[0076] The LBL process refers to the layer-by-layer (LBL) technology, which forms a multilayer film structure by alternately depositing anionic polymers and cationic polymers on the surface of a substrate.
[0077] In the present invention, the cationic polymer is deposited first and then the anionic polymer in the LBL process, that is, the cationic polymer is deposited first and then the anionic polymer in each alternating deposition. The present invention utilizes the anionic and cationic properties of polyelectrolytes to assemble the LATP surface layer by layer, selects a positively charged polyelectrolyte as the first layer for deposition, and then uses a negatively charged polyelectrolyte as the second layer for deposition again. Repeat this process, and form a multilayer film by alternating the deposition of anionic and cationic polyelectrolytes for multiple times.
[0078] Among them:
[0079] The cationic polymer is at least one of PLL (polylysine), PDDA (polydimethyl dieneamine), PPy (polypyrrole) and PEI (polyethyleneimine). In the present invention, the weight average molecular weight M of the cationic polymer is w <100000.
[0080] The anionic polymer is at least one of PSS (i.e., polystyrene sulfonic acid), PEO (i.e., polyethylene oxide), PVDF (i.e., polyvinylidene fluoride) and PAAS (i.e., sodium polyacrylate). In the present invention, the weight average molecular weight M of the anionic polymer is w <100000.
[0081] In the present invention, the polymer deposition method in the LBL process is preferably dipping or spin coating.
[0082] In the present invention, more preferably, the LBL treatment process specifically comprises: immersing the ground LATP obtained in step A) in a cationic polymer solution and an anionic polymer solution in turn, and performing alternating deposition treatment to obtain the modified LATP.
[0083] in:
[0084] The cationic polymer solution is a solution formed by dispersing a cationic polymer in a solvent. The solvent is preferably water or chloroform. The concentration of the cationic polymer solution is preferably 1.0 to 5.0 mol / L, specifically 1.0 mol / L, 1.5 mol / L, 2.0 mol / L, 2.5 mol / L, 3.0 mol / L, 3.5 mol / L, 4.0 mol / L, 4.5 mol / L, 5.0 mol / L.
[0085] The anionic polymer solution is a solution formed by dispersing anionic polymers in a solvent. The solvent is preferably water or chloroform. The concentration of the anionic polymer solution is preferably 1.0 to 5.0 mol / L, specifically 1.0 mol / L, 1.5 mol / L, 2.0 mol / L, 2.5 mol / L, 3.0 mol / L, 3.5 mol / L, 4.0 mol / L, 4.5 mol / L, 5.0 mol / L.
[0086] In the present invention, each time the ground LATP is immersed in the polymer solution, there is no particular restriction on the ratio of the ground LATP obtained in step A) to the polymer solution, as long as the ground LATP can be completely immersed in the polymer solution.
[0087] In the present invention, each time the polymer solution is immersed (whether it is immersed in a cationic polymer solution or an anionic polymer solution), stirring is preferably performed. The stirring temperature is preferably 30 to 50°C, specifically 30°C, 31°C, 32°C, 33°C, 34°C, 35°C, 36°C, 37°C, 38°C, 39°C, 40°C, 41°C, 42°C, 43°C, 44°C, 45°C, 46°C, 47°C, 48°C, 49°C, 50°C. The stirring speed is preferably 200 to 500rpm, specifically 200rpm, 250rpm, 300rpm, 350rpm, 400rpm, 450rpm, 500rpm. The stirring time is preferably 2 to 4h, specifically 2h, 2.5h, 3h, 3.5h, 4h. The above parameter range is selected independently for each stirring condition. In the present invention, the number of repetitions of alternating deposition in the LBL treatment (including the first alternating deposition itself, i.e., the total number of alternating depositions) is preferably 3 to 5 times, specifically 3 times, 4 times, 5 times, and more preferably 3 times. Each round of alternating deposition in the LBL treatment is equivalent to wrapping a layer of polyelectrolyte on the surface of the substrate. In the present invention, after the LBL treatment, washing is preferably performed. The washing liquid used for the washing is preferably water, more preferably deionized water. After the above treatment, a modified LATP is obtained.
[0088] In step B) of the present invention, after the polyelectrolyte layer is formed by LBL treatment, yeast cells are subsequently mixed with the modified LATP particles. Under suitable pH and ionic strength conditions, the negatively charged LATP surface can be fixed on the yeast cells by electrostatic interaction.
[0089] [About Step C]:
[0090] C) dispersing yeast powder in acid solution to obtain yeast powder dispersion.
[0091] In the present invention, the yeast powder is preferably brewer's yeast powder. The present invention has no particular limitation on the source of the yeast powder, and it can be a commercial product. In the present invention, before using the yeast powder, the yeast powder is preferably washed in advance. In the present invention, the detergent used for washing is preferably water and ethanol. After washing, it is dispersed in an acid solution.
[0092] In the present invention, the acid solution is preferably HCl solution. The concentration of the acid solution is preferably 0.05-0.15 mol / L, specifically 0.05 mol / L, 0.06 mol / L, 0.07 mol / L, 0.08 mol / L, 0.09 mol / L, 0.10 mol / L, 0.11 mol / L, 0.12 mol / L, 0.13 mol / L, 0.14 mol / L, 0.15 mol / L, more preferably 0.1 mol / L. The pH of the yeast powder dispersion is preferably adjusted to 2-3 by adding the acid solution, specifically 2.0, 2.5, 3.0.
[0093] The present invention uses yeast cells as the adsorption carrier of LATP. Yeast is a typical and ubiquitous single-cell eukaryotic microorganism with the characteristics of being cheap, easy to obtain, and environmentally friendly. The porous structure of its cell outer wall is very conducive to the loading and dispersion of catalytic active components and can effectively prevent the aggregation of nanomaterials. In addition, the structure of yeast is stable and does not deform, and it is a good adsorbent. The cell outer wall contains abundant functional groups such as hydroxyl, carboxyl, amine, phosphoric acid and amide. Among them, -NH2 undergoes a protonation transformation process in an acidic solution with a pH of about 2 to 3, which makes its surface positively charged. When these positively charged yeast microspheres come into contact with negatively charged LATP, the two can be quickly combined through electrostatic action to form LATP@yeast precursor.
[0094] The present invention has no order restriction on step B) and step C).
[0095] [About Step D]:
[0096] D) mixing the yeast powder dispersion obtained in step C), the modified LATP obtained in step B) and a surfactant, and heating them for reaction to obtain a LATP-yeast-LATP complex.
[0097] In the present invention, the amount of yeast powder in the yeast powder dispersion is preferably 20% to 50% of the mass of the modified LATP, specifically 20%, 23%, 24%, 25%, 30%, 35%, 40%, 45%, or 50%.
[0098] In the present invention, the surfactant is preferably at least one of polyvinyl alcohol (PVA), sodium carboxymethyl cellulose (CMC) and polyvinyl pyrrolidone (PVP). In the present invention, the amount of the surfactant is preferably 5% to 10% of the mass of the modified LATP, specifically 5%, 6%, 6.5%, 7%, 8%, 8.5%, 9%, 10%.
[0099] In the present invention, the yeast powder dispersion obtained in step C), the modified LATP obtained in step B) and the surfactant are preferably mixed by stirring. The stirring is preferably magnetic stirring. The stirring temperature is preferably 40 to 60°C, specifically 40°C, 45°C, 50°C, 55°C, 60°C. The stirring speed is preferably 300 to 500 rpm, specifically 300 rpm, 350 rpm, 450 rpm, 500 rpm. The stirring time is preferably 2 to 6 hours, specifically 2 hours, 3 hours, 4 hours, 5 hours, 6 hours.
[0100] In the present invention, after the mixed solution is obtained by the above mixing, a heating reaction is carried out. Specifically, after the mixed solution is obtained, it can be transferred to a polytetrafluoroethylene-lined hydrothermal reactor for heating reaction. In the present invention, the temperature of the heating reaction is preferably 80 to 150°C, specifically 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, 150°C. The time of the heating reaction is preferably 3 to 7h, specifically 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h, 6.5h, 7h.
[0101] In the present invention, after the above-mentioned heating reaction, post-treatment is preferably performed. The post-treatment preferably includes: cooling, washing and drying. Specifically, after the heating reaction is completed, the product is first naturally cooled to room temperature, and then the obtained precipitate is washed and dried. The washing liquid used in the washing is preferably water and / or ethanol, more preferably washing with water and ethanol in sequence, and washing can be repeated multiple times. After the above-mentioned washing, drying is performed. The drying temperature is preferably 60 to 100°C, specifically 60°C, 70°C, 80°C, 90°C, 100°C. After drying, the LATP-yeast-LATP complex is obtained.
[0102] Yeast forms a hollow porous structure through hydrothermal reaction. When the temperature rises further, the yeast cells are completely inactivated, the hydrated fluid inside the cells escapes and evaporates with the free water, and other organic substances inside (nucleus, mitochondria, etc.) adhere to the inner wall of the yeast microspheres, thus forming a natural hollow porous sphere. The surface of these air microspheres is covered with a large number of functional groups, such as carboxyl, amide, hydroxyl, etc. Under hydrothermal conditions, LATP in the mixed solution is very likely to enter the inactivated yeast cells and effectively connect with the active groups on the inner wall of the yeast cells. The inner and outer surfaces of the yeast cells can be used as LATP loading substrates to participate in the whole process, and the LATP-yeast-LATP complex is obtained.
[0103] [About Step E]:
[0104] E) Sintering the LATP-yeast-LATP complex obtained in step D) to obtain 3D cage-shaped solid electrolyte composite microspheres.
[0105] In the present invention, the sintering treatment is preferably carried out under a protective atmosphere. The present invention has no particular limitation on the type of gas providing the protective atmosphere, and any conventional protective gas in the art may be used, such as nitrogen, helium, argon, etc., more preferably argon.
[0106] In the present invention, the temperature of the sintering treatment is preferably 500-700°C, specifically 500°C, 550°C, 600°C, 650°C, 700°C. The holding time of the sintering treatment is preferably 2-6h, specifically 2h, 3h, 4h, 5h, 6h. After the above sintering treatment, 3D cage-shaped solid electrolyte composite microspheres are obtained.
[0107] Yeast is an elliptical structure with a polysaccharide network structure on its surface. After the heating reaction in step D), it is continuously heated at high temperature in step E), gradually vaporized and released in the form of CO2, CO and H2, so that the yeast is converted into penetrable hollow biochar microspheres with medium and large pores. The loaded LATP is anchored in the inner cavity and surface of the carbon microspheres to form LATP@yeast carbon spheres@LATP composite microspheres with a unique cage structure, which are recorded as 3D cage-like solid electrolyte composite microspheres.
[0108] The present invention also provides a 3D cage-shaped solid electrolyte composite microsphere prepared by the preparation method described in the above technical solution.
[0109] The present invention also provides a method for preparing a solid electrolyte hydrogel, comprising the following steps:
[0110] S1, mixing a hydrophilic ionic monomer, an acrylate compound and a solvent, and irradiating the mixture to obtain a polymer carrier;
[0111] S2, mixing the mother ball, the solvent and the polymer carrier obtained in step S1 to obtain a solid electrolyte hydrogel;
[0112] Wherein, the mother ball is the 3D cage-shaped solid electrolyte composite microsphere described in the above technical solution.
[0113] [About step S1]:
[0114] S1. Mixing a hydrophilic ionic monomer, an acrylate compound and a solvent, and irradiating the mixture to obtain a polymer carrier.
[0115] In the present invention, the hydrophilic ionic monomer is preferably at least one of methacryloyloxyethyl trimethyl ammonium chloride (DMC), dimethyl diallyl ammonium chloride (DMDAAC), acrylic acid (AA), methacrylic acid (MAA), sodium p-styrene sulfonate (SSS) and carboxylic acid betaine (CBAA). In the present invention, the mass ratio of the amount of the hydrophilic ionic monomer to the grinding LATP used in the process of preparing the mother ball is preferably (1-3):1, specifically 1:1, 2:1, 3:1.
[0116] In the present invention, the acrylate compound is preferably at least one of diethylene glycol dimethacrylate (2G), tetraethylene glycol dimethacrylate (4G), non-ethylene glycol dimethacrylate (9G) and tetradecaethylene glycol dimethacrylate (14G). In the present invention, the molar ratio of the acrylate compound to the hydrophilic ionic monomer is preferably 1: (3-5), specifically 1: 3, 1: 4, 1: 5.
[0117] In the present invention, the solvent is preferably at least one of tetrahydrofuran and dimethylformamide. In the present invention, the amount ratio of the hydrophilic ionic monomer to the solvent is preferably (5-15) g: (50-200) mL, specifically 6.5 g: 100 mL, 5 g: 150 mL, 10.5 g: 180 mL, 8.4 g: 80 mL, 12.3 g: 170 mL, 5 g: 50 mL, 10 g: 150 mL, 15 g: 200 mL, 13.8 g: 180 mL, 14.3 g: 150 mL.
[0118] In the present invention, after the hydrophilic ionic monomer, the acrylate compound and the solvent are mixed, the resulting mixture is irradiated. In the present invention, the irradiation is preferably carried out with 60The irradiation temperature is preferably -80 to -50°C, specifically -80°C, -75°C, -70°C, -65°C, -60°C, -55°C, -50°C. The irradiation dose rate is preferably 10 to 15 kGy / h, specifically 10 kGy / h, 11 kGy / h, 12 kGy / h, 13 kGy / h, 14 kGy / h, 15 kGy / h. The irradiation time is preferably 1 to 5 h, specifically 1 h, 2 h, 3 h, 4 h, 5 h.
[0119] The present invention combines the hydrophilic ionic monomer and the acrylate compound through 60 Co-γ-ray irradiation triggers free radical polymerization. γ-rays have high energy and can effectively trigger monomer molecules to produce free radicals, thereby starting the polymerization reaction. At the same time, the polymer chains interact through covalent bonds to form a three-dimensional structure to obtain a polymer carrier.
[0120] [About step S2]:
[0121] S2, mixing the mother ball, the solvent and the polymer carrier obtained in step S1 to obtain a solid electrolyte hydrogel.
[0122] In the present invention, the mother ball is the 3D cage-shaped solid electrolyte composite microsphere described in the above technical solution.
[0123] In the present invention, the solvent is preferably water. The ratio of the water to the ground LATP used in the process of preparing the mother ball is preferably (100-500) mL: 5 g, specifically 100 mL: 5 g, 150 mL: 5 g, 200 mL: 5 g, 250 mL: 5 g, 300 mL: 5 g, 350 mL: 5 g, 400 mL: 5 g, 450 mL: 5 g, 500 mL: 5 g.
[0124] In the present invention, there is no particular limitation on the manner of mixing the mother ball, the solvent and the polymer carrier obtained in step S1, for example, they can be mixed by shaking; during the mixing process, the materials are fully expanded to obtain a solid electrolyte hydrogel.
[0125] The present invention also provides a solid electrolyte hydrogel prepared by the preparation method described in the above technical solution.
[0126] In the preparation process of the solid electrolyte hydrogel of the present invention, a hydrophilic ionic monomer and an acrylate compound are firstly used to 60Co-γ-ray irradiation triggers free radical polymerization reaction; the ray has high energy and can effectively trigger monomer molecules to produce free radicals, thereby starting the polymerization reaction. At the same time, the polymer chains interact through covalent bonds to form a three-dimensional structure, which is coated on the diaphragm to enhance the uniform connection between the two, forming a stable coating that is not easy to fall off. In the process of hydrophilic ion monomer gelation, the hydrophilic groups in the hydrophilic ion monomer form a strong adsorption effect with water molecules, thereby improving the wettability of the 3D cage-like solid electrolyte composite microspheres and contributing to the uniformity of the mixed solution. In short, the application of 3D cage-like solid electrolyte composite microsphere gel in diaphragm coating can improve the ion conductivity, thermal stability and mechanical strength of the battery diaphragm, thereby improving the overall performance and safety of the battery. The application of this composite solid electrolyte gel is expected to show its broad application prospects in the fields of mobile electronic equipment energy storage power supply, new energy vehicles, large-scale energy storage devices, etc.
[0127] The present invention also provides a method for preparing a diaphragm, comprising the following steps:
[0128] coating the hydrogel on the surface of the basement membrane and drying it to obtain a separator;
[0129] Wherein, the hydrogel is the solid electrolyte hydrogel described in the above technical solution.
[0130] In the present invention, the base film is preferably at least one of a PE film and a PP film. In the present invention, the thickness of the base film is preferably 8 to 40 μm, specifically 8 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 36 μm, and 40 μm. In the present invention, when the hydrogel is coated on the surface of the base film, it is preferably coated on both the upper and lower surfaces of the base film. The present invention has no special restrictions on the coating method, and it can be a conventional coating method in the art. In the present invention, the coating thickness is preferably 1 to 5 μm, specifically 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, and 5 μm. After coating, it is dried to obtain a diaphragm.
[0131] The present invention also provides a diaphragm, which is prepared by the preparation method described in the above technical solution.
[0132] The present invention also provides a secondary battery, wherein the diaphragm is the diaphragm described in the above technical solution.
[0133] In the present invention, the positive electrode in the secondary battery can be prepared by the following method: mixing the positive electrode active material, the conductive agent, the binder and the solvent to obtain the positive electrode slurry; then coating the positive electrode slurry on the positive electrode collector, drying and slicing to obtain the positive electrode sheet.
[0134] in:
[0135] The positive electrode active material is preferably at least one of lithium cobalt oxide, lithium manganese oxide and lithium iron phosphate.
[0136] The conductive agent is preferably at least one of carbon black, carbon nanotubes and graphene.
[0137] The binder is preferably at least one of polyvinylidene fluoride (PVDF), polyacrylic acid (PAA), styrene-butadiene rubber (SBR) and hydroxypropyl methylcellulose.
[0138] The solvent is preferably an organic solvent, more preferably at least one of NMP and anhydrous ethanol.
[0139] The mass ratio of the positive electrode material, the conductive agent and the binder is preferably (70-80): (10-20): 10. The amount ratio of the solvent to the positive electrode material is preferably (0.8-0.9): (70-80).
[0140] The mixing process preferably includes: firstly dry-mixing the positive electrode material, the conductive agent and the binder, and then adding a solvent for mixing, so as to obtain a positive electrode slurry.
[0141] The positive electrode current collector is preferably aluminum foil. There are no special restrictions on the operations of coating the positive electrode slurry, drying and slicing, and they can be performed according to conventional means in the art. After the above treatment, a positive electrode sheet is obtained.
[0142] In the present invention, the negative electrode material in the secondary battery can be prepared by the following method: mixing the negative electrode active material, the conductive agent, the binder, the thickener and the solvent to obtain the negative electrode slurry; then, coating it on the negative electrode collector, drying it, and slicing it to obtain the negative electrode sheet.
[0143] in:
[0144] The negative electrode active material is preferably graphite.
[0145] The conductive agent is preferably at least one of carbon black, carbon nanotubes and graphene.
[0146] The binder is preferably at least one of polyvinylidene fluoride (PVDF), polyacrylic acid (PAA), styrene-butadiene rubber (SBR) and hydroxypropyl methylcellulose.
[0147] The thickener is preferably at least one of polyvinyl alcohol (PVA) and carboxymethyl cellulose (CMC).
[0148] The solvent is preferably an organic solvent, more preferably at least one of NMP and anhydrous ethanol.
[0149] The mass ratio of the negative electrode active material, the conductive agent, the binder and the thickener is preferably 100:(1-3):(1-3):(2-4). The amount ratio of the negative electrode active material to the solvent is preferably 100 mg:(0.16-0.18) mL.
[0150] The negative electrode current collector is preferably copper foil. The operations of coating the negative electrode slurry, drying and slicing are not particularly limited and can be performed according to conventional methods in the art. After the above treatment, a negative electrode sheet is obtained.
[0151] In the present invention, the electrolyte in the secondary battery is preferably a LiPF6 electrolyte, that is, an electrolyte formed by dissolving the electrolyte LiPF6 in a solvent. The concentration of the electrolyte is preferably 0.5 to 1.5 mol / L, more preferably 1 mol / L. The solvent in the electrolyte is preferably a mixed solvent of ethylene carbonate (EC) and ethyl methyl carbonate (EMC). The volume ratio of EC to EMC is preferably 1: (1 to 3), more preferably 1: 2.
[0152] In the present invention, the assembly method of the secondary battery is not particularly limited and can be performed according to conventional means in the art. Specifically, the positive electrode sheet, the separator and the negative electrode sheet are stacked in sequence, and then wound into a winding core to obtain an electrode assembly; the wound electrode assembly is placed in a battery housing, and then an electrolyte is added, and the secondary battery is obtained after packaging.
[0153] The present invention provides a 3D cage-shaped solid electrolyte composite microsphere, which has the following beneficial effects:
[0154] 1. The 3D cage-shaped solid electrolyte composite microspheres of the present invention use yeast as a carrier to introduce LATP. The porous structure and surface functional groups of yeast cells effectively prevent the agglomeration of nanomaterials such as LATP and maintain the uniform dispersion of electrolyte materials. The hollow biochar microspheres transformed by yeast can form a penetrable medium and large pore structure, providing abundant channels for ion transmission. This porous structure can promote the rapid migration of ions and improve the ion conductivity of the diaphragm, thereby improving the charge and discharge efficiency of the battery.
[0155] 2. The 3D cage-shaped solid electrolyte composite microspheres provided by the present invention, in which the LATP loaded on the inner cavity and surface of the carbon microspheres can enhance the adsorption capacity of lithium ions, which helps to increase the capacity of the battery and enable the battery to store more energy in the same volume; at the same time, the LATP material and carbon spheres have excellent thermal stability, which helps to maintain battery performance and safety under high temperature conditions.
[0156] 3. The unique cage structure in the 3D cage-shaped solid electrolyte composite microspheres provides mechanical support for LATP and the separator, enhancing the mechanical strength of the separator. During the use of the battery, it can better resist external impact and deformation, improving the safety and stability of the battery.
[0157] 4. The 3D cage-shaped solid electrolyte composite microspheres are transformed from natural yeast and are environmentally friendly. At the same time, their preparation process is relatively simple, which is expected to reduce production costs and provide the possibility for large-scale applications.
[0158] The present invention also provides a solid electrolyte hydrogel, in which the three-dimensional network provides abundant transmission channels for lithium ions, thereby improving the migration rate of ions and the charge and discharge performance of the battery. The gel coating increases the mechanical strength and wettability of the diaphragm, while forming a stable interface between the electrode and the electrolyte, reducing side reactions, improving the cycle stability of the battery, and overall improving the durability and service life of the battery.
[0159] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.
[0160] Example 1
[0161] 1. Preparation of 3D cage-shaped solid electrolyte composite microspheres
[0162] A) Add 900g of anhydrous ethanol as grinding medium into a sand mill, weigh 300g of solid electrolyte Li 1.2 Al 0.2 Ti 1.8 (PO4)3 was added to a sand mill for sand grinding. The grinding balls used in the sand mill were zirconia balls (grinding ball diameter was 0.3 mm). The speed of the sand mill was set to 1500 r / min and the grinding time was 4 h. LATP slurry (D50 was 251 nm) was obtained by grinding. The slurry was then dried and stored to obtain ground LATP.
[0163] B) Weigh 5 g of the ground LATP obtained in step A) and perform LBL treatment, specifically: first immerse in a PDDA solution (concentration of 2 mol / L, solvent is water) and stir at 37°C and 350 rpm for 3 h, then immerse in a PSS solution (concentration of 2 mol / L, solvent is water) and stir at 37°C for 3 h, which is the first alternating deposition. Repeat the above alternating deposition steps for a total of 3 alternating depositions, and then wash twice with deionized water to obtain modified LATP.
[0164] C) 0.48 g of brewer's yeast powder was weighed, washed with water and ethanol in sequence, and then dispersed in a HCl solution (with a concentration of 0.1 mol / L), and the pH was adjusted to 2.0 to obtain a yeast dispersion.
[0165] D) Under magnetic stirring, 2 g of the modified LATP obtained in step B) and 0.13 g of the surfactant PVA were added to the yeast dispersion, and magnetic stirring was performed at 50° C. and 350 rpm for 3 h to obtain a mixed solution. Then, the mixed solution was transferred to a polytetrafluoroethylene-lined hydrothermal reactor and reacted at 90° C. for 4 h. Then, it was naturally cooled to room temperature, and the obtained precipitate was repeatedly washed with deionized water and ethanol, and dried in a 60° C. oven to obtain a LATP-yeast-LATP complex.
[0166] E) placing the LATP-yeast-LATP complex obtained in step D) in a tubular heating furnace and continuously heating at 500° C. for 3 h under argon protection to obtain LATP@yeast carbon sphere@LATP composite microspheres, i.e., 3D cage-shaped solid electrolyte composite microspheres.
[0167] The obtained 3D cage-like solid electrolyte composite microsphere samples were characterized by microstructure. Figure 1 As shown, it can be seen that the obtained sample is in the shape of microspheres.
[0168] 2. Preparation of solid electrolyte hydrogel
[0169] S1, 6.5g of hydrophilic ionic monomer DMC, 3.58g of acrylate compound 2G and 100mL of dimethylformamide were mixed, and then the resulting mixture was heated at -78°C using 60 The polymer carrier was obtained by irradiating with Co-γ rays (dose rate: 11 kGy / h) for 3 h.
[0170] S2. Mix the 3D cage-shaped solid electrolyte composite microspheres with 200 mL of water, and then mix and shake them with the polymer carrier to make them fully swell to obtain a solid electrolyte hydrogel.
[0171] 3. Preparation of diaphragm
[0172] The solid electrolyte hydrogel was evenly coated on the upper and lower surfaces of a PP base film with a thickness of 11 μm (the upper and lower surfaces were coated with the same thickness), and dried to obtain a solid electrolyte separator with a thickness of 5 μm.
[0173] The microscopic morphology of the solid electrolyte hydrogel coated on the separator was characterized. Figure 2 As shown, it can be seen that the solid electrolyte is evenly dispersed on the surface of the separator.
[0174] 4. Preparation of secondary batteries
[0175] K1. Lithium cobalt oxide, carbon black and PVDF are dry-mixed in a mass ratio of 70:20:10, and NMP solvent is added to prepare a positive electrode slurry, which is coated on a positive electrode current collector aluminum foil, dried and sliced to obtain a positive electrode sheet.
[0176] K2. Mix the negative electrode active material (graphite), carbon black, PVDF, PVA and NMP, wherein the mass ratio of the negative electrode active materials graphite, carbon black, PVDF and PVA is 100:1:3:2, to obtain a negative electrode slurry; evenly coat the negative electrode slurry on the negative electrode collector copper foil, dry and slice it to obtain a negative electrode sheet.
[0177] K3. Stack the positive electrode sheet, the separator and the negative electrode sheet in sequence, and then wind them into a core to obtain an electrode assembly; put the wound electrode assembly into the battery shell, add electrolyte (LiPF6 electrolyte with a concentration of 1 mol / L, the solvents are EC and EMC, and the volume ratio of EC to EMC is 1:2), and after packaging, a secondary battery is obtained.
[0178] Example 2
[0179] 1. Preparation of 3D cage-shaped solid electrolyte composite microspheres
[0180] A) Add 1200g of anhydrous ethanol as grinding medium into a sand mill, weigh 400g of solid electrolyte Li 1.3 Al 0.3 Ti 1.7 (PO4)3 was added to a sand mill for sand grinding. The grinding balls used in the sand mill were zirconia balls (grinding ball diameter was 0.4 mm). The speed of the sand mill was set to 1900 r / min and the grinding time was 10 h. LATP slurry (D50 was 142 nm) was obtained by grinding. The slurry was then dried and stored to obtain ground LATP.
[0181] B) Weigh 5 g of the ground LATP obtained in step A) and perform LBL treatment, specifically: first immerse in a PPy solution (concentration of 3 mol / L, solvent is water) and stir magnetically at 40°C for 4 h, then immerse in a PVDF solution (concentration of 3 mol / L, solvent is water) and stir at 40°C and 200 rpm for 4 h, which is the first alternating deposition. Repeat the above alternating deposition steps for a total of 3 alternating depositions, and then wash twice with deionized water to obtain modified LATP.
[0182] C) 1 g of brewer's yeast powder was weighed, washed with water and ethanol in sequence, and then dispersed in a HCl solution (with a concentration of 0.1 mol / L), and the pH was adjusted to 2.5 to obtain a yeast dispersion.
[0183] D) Under magnetic stirring, 5 g of the modified LATP obtained in step B) and 0.38 g of the surfactant PVP were added to the yeast dispersion, and magnetic stirring was performed at 40° C. and 300 rpm for 2 h to obtain a mixed solution. Then, the mixed solution was transferred to a polytetrafluoroethylene-lined hydrothermal reactor and reacted at 80° C. for 5 h. Then, it was naturally cooled to room temperature, and the obtained precipitate was repeatedly washed with deionized water and ethanol, and dried in an oven at 80° C. to obtain a LATP-yeast-LATP complex.
[0184] E) placing the LATP-yeast-LATP complex obtained in step D) in a tubular heating furnace and continuously heating at 600° C. for 5 h under argon protection to obtain LATP@yeast carbon sphere@LATP composite microspheres, i.e., 3D cage-shaped solid electrolyte composite microspheres.
[0185] 2. Preparation of solid electrolyte hydrogel
[0186] S1, 5g of hydrophilic ionic monomer DMDAAC, 1.68g of acrylate compound 4G and 150mL of dimethylformamide were mixed, and then the resulting mixture was heated at -65°C using 60 The polymer carrier was obtained by irradiating with Co-γ rays (dose rate: 13 kGy / h) for 2 h.
[0187] S2. Mix the 3D cage-shaped solid electrolyte composite microspheres with 500 mL of water, and then mix and shake them with the polymer carrier to make them fully swell to obtain a solid electrolyte hydrogel.
[0188] 3. Preparation of diaphragm
[0189] The solid electrolyte hydrogel was evenly coated on the upper and lower surfaces of a PP base film with a thickness of 22 μm (the upper and lower surfaces were coated with the same thickness), and dried to obtain a solid electrolyte separator with a thickness of 3 μm.
[0190] 4. Preparation of secondary batteries
[0191] K1. Lithium manganate, carbon nanotubes and PAA are dry-mixed in a mass ratio of 75:15:10, and anhydrous ethanol is added to prepare a positive electrode slurry, which is coated on a positive electrode current collector aluminum foil, dried and sliced to obtain a positive electrode sheet.
[0192] K2. Mix the negative electrode active material (graphite), carbon nanotubes, PAA, CMC and anhydrous ethanol, wherein the mass ratio of the negative electrode active material graphite, carbon nanotubes, PAA and CMC is 100:1:1:2, to obtain a negative electrode slurry; evenly coat the negative electrode slurry on the negative electrode current collector copper foil, dry and slice it to obtain a negative electrode sheet.
[0193] K3. Stack the positive electrode sheet, the separator and the negative electrode sheet in sequence, and then wind them into a core to obtain an electrode assembly; put the wound electrode assembly into the battery shell, add electrolyte (LiPF6 electrolyte with a concentration of 1 mol / L, the solvents are EC and EMC, and the volume ratio of EC to EMC is 1:2), and after packaging, a secondary battery is obtained.
[0194] Example 3
[0195] 1. Preparation of 3D cage-shaped solid electrolyte composite microspheres
[0196] A) Add 1500g of water as grinding medium into a sand mill, weigh 500g of solid electrolyte Li 1.3 Al 0.3 Ti 1.7 (PO4)3 was added to a sand mill for sand grinding. The grinding balls used in the sand mill were zirconium oxide balls (grinding ball diameter was 0.3 mm). The speed of the sand mill was set to 1100 r / min and the grinding time was 12 h. LATP slurry (D50 was 187 nm) was obtained by grinding. The slurry was then dried and stored to obtain ground LATP.
[0197] B) Weigh 5 g of the ground LATP obtained in step A) and perform LBL treatment, specifically: first immerse in PEI solution (concentration of 3.5 mol / L, solvent is chloroform) at 42°C with magnetic stirring for 2.5 h, and then immerse in PEO solution (concentration of 3.5 mol / L, solvent is chloroform) at 42°C and 450 rpm with stirring for 2.5 h, which is the first alternating deposition. Repeat the above alternating deposition steps for a total of 3 alternating depositions, and then wash twice with deionized water to obtain modified LATP.
[0198] C) 1.8 g of brewer's yeast powder was weighed, washed with water and ethanol in sequence, and then dispersed in a HCl solution (with a concentration of 0.1 mol / L), and the pH was adjusted to 3 to obtain a yeast dispersion.
[0199] D) Under magnetic stirring, 4.8 g of the modified LATP obtained in step B) and 0.41 g of the surfactant CMC were added to the yeast dispersion, and magnetic stirring was performed at 55° C. and 450 rpm for 3.5 h to obtain a mixed solution. Then, the mixed solution was transferred to a polytetrafluoroethylene-lined hydrothermal reactor and reacted at 100° C. for 6.5 h. Then, it was naturally cooled to room temperature, and the obtained precipitate was repeatedly washed with deionized water and ethanol, and dried in an oven at 80° C. to obtain a LATP-yeast-LATP complex.
[0200] E) The LATP-yeast-LATP complex obtained in step D) is placed in a tubular heating furnace and continuously heated at 650° C. for 4 hours under argon protection to obtain LATP@yeast carbon sphere@LATP composite microspheres, i.e., 3D cage-shaped solid electrolyte composite microspheres.
[0201] 2. Preparation of solid electrolyte hydrogel
[0202] S1, 10.5g of hydrophilic ionic monomer AA, 14.11g of acrylate compound 9G and 180mL of tetrahydrofuran were mixed, and then the resulting mixture was heated at -80°C using 60 The polymer carrier was obtained by irradiating with Co-γ rays (dose rate: 13 kGy / h) for 3 h.
[0203] S2. Mix the 3D cage-shaped solid electrolyte composite microspheres with 300 mL of water, and then mix and shake them with the polymer carrier to make them fully swell to obtain a solid electrolyte hydrogel.
[0204] 3. Preparation of diaphragm
[0205] The solid electrolyte hydrogel was evenly coated on the upper and lower surfaces of a PP base film with a thickness of 13 μm (the upper and lower surfaces were coated with the same thickness), and dried to obtain a solid electrolyte separator with a thickness of 4 μm.
[0206] 4. Preparation of secondary batteries
[0207] K1. Lithium iron phosphate, carbon nanotubes and SBR are dry-mixed in a mass ratio of 78:12:10, and NMP is added to prepare a positive electrode slurry, which is coated on a positive electrode current collector aluminum foil, dried and sliced to obtain a positive electrode sheet.
[0208] K2. Mix the negative electrode active material (graphite), carbon nanotubes, SBR, CMC and NMP, wherein the mass ratio of the negative electrode active material graphite, carbon nanotubes, SBR and CMC is 100:1:1:4, to obtain a negative electrode slurry; evenly coat the negative electrode slurry on the negative electrode current collector copper foil, dry and slice it to obtain a negative electrode sheet.
[0209] K3. Stack the positive electrode sheet, the separator and the negative electrode sheet in sequence, and then wind them into a core to obtain an electrode assembly; put the wound electrode assembly into the battery shell, add electrolyte (LiPF6 electrolyte with a concentration of 1 mol / L, the solvents are EC and EMC, and the volume ratio of EC to EMC is 1:2), and after packaging, a secondary battery is obtained.
[0210] Example 4
[0211] 1. Preparation of 3D cage-shaped solid electrolyte composite microspheres
[0212] A) Add 1200g NMP as grinding medium into a sand mill, weigh 400g solid electrolyte Li 1.5 Al 0.5 Ti 1.5 (PO4)3 was added to a sand mill for sand grinding. The grinding balls used in the sand mill were zirconium oxide balls (grinding ball diameter was 0.5 mm). The speed of the sand mill was set to 1400 r / min and the grinding time was 3 h. LATP slurry (D50 was 327 nm) was obtained by grinding. The slurry was then dried and stored to obtain ground LATP.
[0213] B) Weigh 5 g of the ground LATP obtained in step A) and perform LBL treatment, specifically: first immerse in a PLL solution (concentration of 4.5 mol / L, solvent is chloroform) at 34°C with magnetic stirring for 3.5 h, then immerse in a PAAS solution (concentration of 4.5 mol / L, solvent is chloroform) at 34°C and 450 rpm with stirring for 3.5 h, which is the first alternating deposition. Repeat the above alternating deposition steps for a total of 3 alternating depositions, and then wash twice with deionized water to obtain modified LATP.
[0214] C) 2.2 g of brewer's yeast powder was weighed, washed with water and ethanol in sequence, and then dispersed in HCl solution (concentration: 0.1 mol / L), and the pH was adjusted to 2.5 to obtain a yeast dispersion.
[0215] D) Under magnetic stirring, 5.5 g of the modified LATP obtained in step B) and 0.51 g of the surfactant PVP were added to the yeast dispersion, and magnetic stirring was performed at 50° C. and 400 rpm for 5 h to obtain a mixed solution. Then, the mixed solution was transferred to a polytetrafluoroethylene-lined hydrothermal reactor and reacted at 120° C. for 4.5 h. Then, it was naturally cooled to room temperature, and the obtained precipitate was repeatedly washed with deionized water and ethanol, and dried in an oven at 100° C. to obtain a LATP-yeast-LATP complex.
[0216] E) The LATP-yeast-LATP complex obtained in step D) is placed in a tubular heating furnace and continuously heated at 600° C. for 5.5 h under argon protection to obtain LATP@yeast carbon sphere@LATP composite microspheres, i.e., 3D cage-shaped solid electrolyte composite microspheres.
[0217] 2. Preparation of solid electrolyte hydrogel
[0218] S1, 8.4g of hydrophilic ionic monomer SSS, 2.41g of acrylate compound 14G and 80mL of tetrahydrofuran were mixed, and then the resulting mixture was heated at -55°C using 60 The polymer carrier was obtained by irradiating with Co-γ rays (dose rate: 12 kGy / h) for 4 h.
[0219] S2. Mix the 3D cage-shaped solid electrolyte composite microspheres with 400 mL of water, and then mix and shake them with the polymer carrier to make them fully swell to obtain a solid electrolyte hydrogel.
[0220] 3. Preparation of diaphragm
[0221] The solid electrolyte hydrogel was evenly coated on the upper and lower surfaces of a 35 μm thick PE base film (the upper and lower surfaces were coated with the same thickness), and dried to obtain a solid electrolyte separator with a thickness of 2.5 μm.
[0222] 4. Preparation of secondary batteries
[0223] K1. Lithium iron phosphate, carbon nanotubes and hydroxypropyl methylcellulose are dry-mixed in a mass ratio of 76:14:10, and NMP is added to prepare a positive electrode slurry, which is coated on a positive electrode current collector aluminum foil, dried and sliced to obtain a positive electrode sheet.
[0224] K2. Mix the negative electrode active material (graphite), carbon nanotubes, hydroxypropyl methylcellulose, PVA and NMP, wherein the mass ratio of the negative electrode active material graphite, carbon nanotubes, hydroxypropyl methylcellulose and PVA is 100:1:3:2, to obtain a negative electrode slurry; evenly coat the negative electrode slurry on the negative electrode current collector copper foil, dry and slice it to obtain a negative electrode sheet.
[0225] K3. Stack the positive electrode sheet, the separator and the negative electrode sheet in sequence, and then wind them into a core to obtain an electrode assembly; put the wound electrode assembly into the battery shell, add electrolyte (LiPF6 electrolyte with a concentration of 1 mol / L, the solvents are EC and EMC, and the volume ratio of EC to EMC is 1:2), and after packaging, a secondary battery is obtained.
[0226] Example 5
[0227] 1. Preparation of 3D cage-shaped solid electrolyte composite microspheres
[0228] A) Add 1500g of water as grinding medium into a sand mill, weigh 500g of solid electrolyte Li 1.4 Al 0.4 Ti 1.6 (PO4)3 was added to a sand mill for sand grinding. The grinding balls used in the sand mill were zirconia balls (grinding ball diameter was 0.7 mm). The speed of the sand mill was set to 1700 r / min and the grinding time was 11 h. LATP slurry (D50 was 353 nm) was obtained by grinding. The slurry was then dried and stored to obtain ground LATP.
[0229] B) Weigh 5 g of the ground LATP obtained in step A) and perform LBL treatment, specifically: first immerse in a PLL solution (concentration of 1.5 mol / L, solvent is water) at 50°C with magnetic stirring for 3 h, then immerse in a PAAS solution (concentration of 1.5 mol / L, solvent is water) at 50°C and 300 rpm with stirring for 3 h, which is the first alternating deposition. Repeat the above alternating deposition steps for a total of 3 alternating depositions, and then wash twice with deionized water to obtain modified LATP.
[0230] C) 1.5 g of brewer's yeast powder was weighed, washed with water and ethanol in sequence, and then dispersed in a HCl solution (with a concentration of 0.1 mol / L), and the pH was adjusted to 3 to obtain a yeast dispersion.
[0231] D) Under magnetic stirring, 3.4 g of the modified LATP obtained in step B) and 0.29 g of the surfactant PVP were added to the yeast dispersion, and magnetic stirring was performed at 45° C. and 400 rpm for 5 h to obtain a mixed solution. Then, the mixed solution was transferred to a polytetrafluoroethylene-lined hydrothermal reactor and reacted at 140° C. for 5.5 h. Then, it was naturally cooled to room temperature, and the obtained precipitate was repeatedly washed with deionized water and ethanol, and dried in a 90° C. oven to obtain a LATP-yeast-LATP complex.
[0232] E) The LATP-yeast-LATP complex obtained in step D) is placed in a tubular heating furnace and continuously heated at 550° C. for 6 hours under argon protection to obtain LATP@yeast carbon sphere@LATP composite microspheres, i.e., 3D cage-shaped solid electrolyte composite microspheres.
[0233] 2. Preparation of solid electrolyte hydrogel
[0234] S1, 12.3g of hydrophilic ionic monomer SSS, 2.82g of acrylate compound 14G and 170mL of tetrahydrofuran were mixed, and then the resulting mixture was heated at -60°C using 60 The polymer carrier was obtained by irradiating with Co-γ rays (dose rate: 14 kGy / h) for 4.5 h.
[0235] S2. Mix the 3D cage-shaped solid electrolyte composite microspheres with 250 mL of water, and then mix and shake them with the polymer carrier to make them fully swell to obtain a solid electrolyte hydrogel.
[0236] 3. Preparation of diaphragm
[0237] The solid electrolyte hydrogel was evenly coated on the upper and lower surfaces of a PE-based film with a thickness of 19 μm (the upper and lower surfaces were coated with the same thickness), and dried to obtain a solid electrolyte separator with a thickness of 2.7 μm.
[0238] 4. Preparation of secondary batteries
[0239] K1. Lithium manganate, graphene and PAA are dry-mixed in a mass ratio of 74:16:10, and anhydrous ethanol is added to prepare a positive electrode slurry, which is coated on the positive electrode current collector aluminum foil, dried and sliced to obtain a positive electrode sheet.
[0240] K2. Mix the negative electrode active material (graphite), graphene, PAA, CMC and anhydrous ethanol, wherein the mass ratio of the negative electrode active materials graphite, graphene, PAA and CMC is 100:3:3:4, to obtain a negative electrode slurry; evenly coat the negative electrode slurry on the negative electrode current collector copper foil, dry and slice it to obtain a negative electrode sheet.
[0241] K3. Stack the positive electrode sheet, the separator and the negative electrode sheet in sequence, and then wind them into a core to obtain an electrode assembly; put the wound electrode assembly into the battery shell, add electrolyte (LiPF6 electrolyte with a concentration of 1 mol / L, the solvents are EC and EMC, and the volume ratio of EC to EMC is 1:2), and after packaging, a secondary battery is obtained.
[0242] Example 6
[0243] 1. Preparation of 3D cage-shaped solid electrolyte composite microspheres
[0244] A) Add 1500g of anhydrous ethanol as grinding medium into a sand mill, weigh 500g of solid electrolyte Li 1.1 Al 0.1 Ti 1.9 (PO4)3 was added to a sand mill for sand grinding. The grinding balls used in the sand mill were zirconia balls (grinding ball diameter was 0.6 mm). The speed of the sand mill was set to 500 r / min and the grinding time was 12 h. LATP slurry (D50 was 391 nm) was obtained by grinding. The slurry was then dried and stored to obtain ground LATP.
[0245] B) Weigh 5 g of the ground LATP obtained in step A) and perform LBL treatment, specifically: first immerse in a PEI solution (concentration of 5 mol / L, solvent is water) at 50°C with magnetic stirring for 2 h, then immerse in a PSS solution (concentration of 5 mol / L, solvent is water) at 50°C and 200 rpm with stirring for 2 h, which is the first alternating deposition. Repeat the above alternating deposition steps for a total of 3 alternating depositions, and then wash twice with deionized water to obtain modified LATP.
[0246] C) 2.75 g of brewer's yeast powder was weighed, washed with water and ethanol in sequence, and then dispersed in a HCl solution (with a concentration of 0.1 mol / L), and the pH was adjusted to 3 to obtain a yeast dispersion.
[0247] D) Under magnetic stirring, 5.5 g of the modified LATP obtained in step B) and 0.45 g of the surfactant CMC were added to the yeast dispersion, and magnetic stirring was performed at 40° C. and 300 rpm for 6 h to obtain a mixed solution. Then, the mixed solution was transferred to a polytetrafluoroethylene-lined hydrothermal reactor and reacted at 80° C. for 7 h. Then, it was naturally cooled to room temperature, and the obtained precipitate was repeatedly washed with deionized water and ethanol, and dried in a 60° C. oven to obtain a LATP-yeast-LATP complex.
[0248] E) placing the LATP-yeast-LATP complex obtained in step D) in a tubular heating furnace and continuously heating at 500° C. for 6 h under argon protection to obtain LATP@yeast carbon sphere@LATP composite microspheres, i.e., 3D cage-shaped solid electrolyte composite microspheres.
[0249] 2. Preparation of solid electrolyte hydrogel
[0250] S1, 5g of hydrophilic ionic monomer AA, 1.67g of acrylate compound 14G and 50mL of dimethylformamide were mixed, and then the resulting mixture was heated at -80°C using 60 The polymer carrier was obtained by irradiating with Co-γ rays (dose rate: 10 kGy / h) for 1 h.
[0251] S2. Mix the 3D cage-shaped solid electrolyte composite microspheres with 100 mL of water, and then mix and shake them with the polymer carrier to make them fully swell to obtain a solid electrolyte hydrogel.
[0252] 3. Preparation of diaphragm
[0253] The solid electrolyte hydrogel was evenly coated on the upper and lower surfaces of a PE-based film with a thickness of 8 μm (the upper and lower surfaces were coated with the same thickness), and dried to obtain a solid electrolyte separator with a thickness of 1 μm.
[0254] 4. Preparation of secondary batteries
[0255] K1. Lithium iron phosphate, carbon black and hydroxypropyl methylcellulose are dry-mixed in a mass ratio of 70:20:10, and anhydrous ethanol is added to prepare a positive electrode slurry, which is coated on a positive electrode current collector aluminum foil, dried and sliced to obtain a positive electrode sheet.
[0256] K2. Mix the negative electrode active material (graphite), carbon black, hydroxypropyl methylcellulose, PVA and anhydrous ethanol, wherein the mass ratio of the negative electrode active material graphite, carbon black, hydroxypropyl methylcellulose and PVA is 100:1:1:2, to obtain a negative electrode slurry; evenly coat the negative electrode slurry on the negative electrode current collector copper foil, dry and slice it to obtain a negative electrode sheet.
[0257] K3. Stack the positive electrode sheet, the separator and the negative electrode sheet in sequence, and then wind them into a core to obtain an electrode assembly; put the wound electrode assembly into the battery shell, add electrolyte (LiPF6 electrolyte with a concentration of 1 mol / L, the solvents are EC and EMC, and the volume ratio of EC to EMC is 1:2), and after packaging, a secondary battery is obtained.
[0258] Example 7
[0259] 1. Preparation of 3D cage-shaped solid electrolyte composite microspheres
[0260] A) Add 900g NMP as grinding medium into a sand mill, weigh 300g solid electrolyte Li 1.3 Al 0.3 Ti 1.7 (PO4)3 was added to a sand mill for sand grinding. The grinding balls used in the sand mill were zirconia balls (grinding ball diameter was 0.4 mm). The speed of the sand mill was set to 1800 r / min and the grinding time was 6 h. LATP slurry (D50 was 168 nm) was obtained by grinding. The slurry was then dried and stored to obtain ground LATP.
[0261] B) Weigh 5 g of the ground LATP obtained in step A) and perform LBL treatment, specifically: first immerse in a PPy solution (concentration of 2.5 mol / L, solvent is chloroform) at 45°C with magnetic stirring for 3 h, then immerse in a PEI solution (concentration of 2.5 mol / L, solvent is chloroform) at 45°C and 250 rpm with stirring for 3 h, which is the first alternating deposition. Repeat the above alternating deposition steps for a total of 3 alternating depositions, and then wash twice with deionized water to obtain modified LATP.
[0262] C) 0.8 g of brewer's yeast powder was weighed, washed with water and ethanol in sequence, and then dispersed in a HCl solution (with a concentration of 0.1 mol / L), and the pH was adjusted to 2.5 to obtain a yeast dispersion.
[0263] D) Under magnetic stirring, 3.9 g of the modified LATP obtained in step B) and 0.37 g of the surfactant PVP were added to the yeast dispersion, and magnetic stirring was performed at 50° C. and 350 rpm for 4 h to obtain a mixed solution. Then, the mixed solution was transferred to a polytetrafluoroethylene-lined hydrothermal reactor and reacted at 110° C. for 5 h. Then, it was naturally cooled to room temperature, and the obtained precipitate was repeatedly washed with deionized water and ethanol, and dried in a 70° C. oven to obtain a LATP-yeast-LATP complex.
[0264] E) placing the LATP-yeast-LATP complex obtained in step D) in a tubular heating furnace and continuously heating at 550° C. for 4 h under argon protection to obtain LATP@yeast carbon sphere@LATP composite microspheres, i.e., 3D cage-shaped solid electrolyte composite microspheres.
[0265] 2. Preparation of solid electrolyte hydrogel
[0266] S1, 10g of hydrophilic ionic monomer MAA, 5.45g of acrylate compound 4G and 150mL of tetrahydrofuran were mixed, and then the resulting mixture was heated at -65°C using 60 The polymer carrier was obtained by irradiating with Co-γ rays (dose rate: 10 kGy / h) for 2 h.
[0267] S2. Mix the 3D cage-shaped solid electrolyte composite microspheres with 300 mL of water, and then mix and shake them with the polymer carrier to make them fully swell to obtain a solid electrolyte hydrogel.
[0268] 3. Preparation of diaphragm
[0269] The solid electrolyte hydrogel was evenly coated on the upper and lower surfaces of a PE-based film with a thickness of 17 μm (the upper and lower surfaces were coated with the same thickness), and dried to obtain a solid electrolyte separator with a thickness of 3.5 μm.
[0270] 4. Preparation of secondary batteries
[0271] K1. Lithium cobalt oxide, graphene and PVDF are dry-mixed in a mass ratio of 75:15:10, and anhydrous ethanol is added to prepare a positive electrode slurry, which is coated on the positive electrode current collector aluminum foil, dried and sliced to obtain a positive electrode sheet.
[0272] K2. Mix the negative electrode active material (graphite), graphene, PVDF, PVA and anhydrous ethanol, wherein the mass ratio of the negative electrode active material graphite, graphene, PVA and anhydrous ethanol is 100:1:1:2, to obtain a negative electrode slurry; evenly coat the negative electrode slurry on the negative electrode current collector copper foil, dry and slice it to obtain a negative electrode sheet.
[0273] K3. Stack the positive electrode sheet, the separator and the negative electrode sheet in sequence, and then wind them into a core to obtain an electrode assembly; put the wound electrode assembly into the battery shell, add electrolyte (LiPF6 electrolyte with a concentration of 1 mol / L, the solvents are EC and EMC, and the volume ratio of EC to EMC is 1:2), and after packaging, a secondary battery is obtained.
[0274] Example 8
[0275] 1. Preparation of 3D cage-shaped solid electrolyte composite microspheres
[0276] A) Add 1500g of anhydrous ethanol as grinding medium into a sand mill, weigh 500g of solid electrolyte Li 1.9 Al 0.9 Ti 1.1(PO4)3 was added to a sand mill for sand grinding. The grinding balls used in the sand mill were zirconia balls (grinding ball diameter was 0.3 mm). The speed of the sand mill was set to 2000 r / min and the grinding time was 2 h. LATP slurry (D50 was 243 nm) was obtained by grinding. The slurry was then dried and stored to obtain ground LATP.
[0277] B) Weigh 5 g of the ground LATP obtained in step A) and perform LBL treatment, specifically: first immerse in a PPy solution (concentration of 1 mol / L, solvent is water) at 30°C with magnetic stirring for 4 h, then immerse in a PEO solution (concentration of 1 mol / L, solvent is water) at 30°C and 500 rpm with stirring for 2 h, which is the first alternating deposition. Repeat the above alternating deposition steps for a total of 3 alternating depositions, and then wash twice with deionized water to obtain modified LATP.
[0278] C) 0.96 g of brewer's yeast powder was weighed, washed with water and ethanol in sequence, and then dispersed in a HCl solution (with a concentration of 0.1 mol / L), and the pH was adjusted to 2 to obtain a yeast dispersion.
[0279] D) Under magnetic stirring, 4.2 g of the modified LATP obtained in step B) and 0.24 g of the surfactant PVA were added to the yeast dispersion, and magnetic stirring was performed at 60° C. and 500 rpm for 2 h to obtain a mixed solution. Then, the mixed solution was transferred to a polytetrafluoroethylene-lined hydrothermal reactor and reacted at 150° C. for 3 h. Then, it was naturally cooled to room temperature, and the obtained precipitate was repeatedly washed with deionized water and ethanol, and dried in an oven at 100° C. to obtain a LATP-yeast-LATP complex.
[0280] E) placing the LATP-yeast-LATP complex obtained in step D) in a tubular heating furnace and continuously heating at 700° C. for 2 h under argon protection to obtain LATP@yeast carbon sphere@LATP composite microspheres, i.e., 3D cage-shaped solid electrolyte composite microspheres.
[0281] 2. Preparation of solid electrolyte hydrogel
[0282] S1, 15g of hydrophilic ionic monomer DMDAAC, 6.89g of acrylate compound 2G and 200mL of tetrahydrofuran were mixed, and then the resulting mixture was heated at -50°C using 60 The polymer carrier was obtained by irradiating with Co-γ rays (dose rate: 15 kGy / h) for 5 h.
[0283] S2. Mix the 3D cage-shaped solid electrolyte composite microspheres with 500 mL of water, and then mix and shake them with the polymer carrier to make them fully swell to obtain a solid electrolyte hydrogel.
[0284] 3. Preparation of diaphragm
[0285] The solid electrolyte hydrogel was evenly coated on the upper and lower surfaces of a PP base film with a thickness of 40 μm (the upper and lower surfaces were coated with the same thickness), and dried to obtain a solid electrolyte separator with a thickness of 5 μm.
[0286] 4. Preparation of secondary batteries
[0287] K1. Lithium cobalt oxide, carbon black and SBR are dry-mixed in a mass ratio of 80:10:10, and NMP is added to prepare a positive electrode slurry, which is coated on a positive electrode current collector aluminum foil, dried and sliced to obtain a positive electrode sheet.
[0288] K2. Mix the negative electrode active material (graphite), carbon black, SBR, PVA and NMP, wherein the ratio of the negative electrode active materials graphite, carbon black, SBR and PVA is 100:3:3:4, to obtain a negative electrode slurry; evenly coat the negative electrode slurry on the negative electrode current collector copper foil, dry and slice it to obtain a negative electrode sheet.
[0289] K3. Stack the positive electrode sheet, the separator and the negative electrode sheet in sequence, and then wind them into a core to obtain an electrode assembly; put the wound electrode assembly into the battery shell, add electrolyte (LiPF6 electrolyte with a concentration of 1 mol / L, the solvents are EC and EMC, and the volume ratio of EC to EMC is 1:2), and after packaging, a secondary battery is obtained.
[0290] Example 9
[0291] 1. Preparation of 3D cage-shaped solid electrolyte composite microspheres
[0292] A) Add 1500g of anhydrous ethanol as grinding medium into a sand mill, weigh 500g of solid electrolyte Li 1.6 Al 0.6 Ti 1.4 (PO4)3 was added to a sand mill for sand grinding. The grinding balls used in the sand mill were zirconia balls (the diameter of the grinding balls was 0.6 mm). The speed of the sand mill was set to 850 r / min and the grinding time was 12 h. LATP slurry (D50 was 392 nm) was obtained by grinding. The slurry was then dried and stored to obtain ground LATP.
[0293] B) Weigh 5 g of the ground LATP obtained in step A) and perform LBL treatment, specifically: first immerse in a PDDA solution (concentration of 4 mol / L, solvent is chloroform) at 43°C with magnetic stirring for 2.5 h, then immerse in a PAAS solution (concentration of 4 mol / L, solvent is chloroform) at 43°C and 420 rpm with stirring for 2.5 h, which is the first alternating deposition. Repeat the above alternating deposition steps for a total of 3 alternating depositions, and then wash twice with deionized water to obtain modified LATP.
[0294] C) 2.8 g of brewer's yeast powder was weighed, washed with water and ethanol in sequence, and then dispersed in a HCl solution (with a concentration of 0.1 mol / L), and the pH was adjusted to 3 to obtain a yeast dispersion.
[0295] D) Under magnetic stirring, 5.6 g of the modified LATP obtained in step B) and 0.56 g of the surfactant CMC were added to the yeast dispersion, and magnetic stirring was performed at 45° C. and 360 rpm for 3 h to obtain a mixed solution. Then, the mixed solution was transferred to a polytetrafluoroethylene-lined hydrothermal reactor and reacted at 90° C. for 7 h. Then, it was naturally cooled to room temperature, and the obtained precipitate was repeatedly washed with deionized water and ethanol, and dried in an oven at 100° C. to obtain a LATP-yeast-LATP complex.
[0296] E) The LATP-yeast-LATP complex obtained in step D) is placed in a tubular heating furnace and continuously heated at 680° C. for 5.5 h under argon protection to obtain LATP@yeast carbon sphere@LATP composite microspheres, i.e., 3D cage-shaped solid electrolyte composite microspheres.
[0297] 2. Preparation of solid electrolyte hydrogel
[0298] S1, 13.8g of hydrophilic ionic monomer CBAA, 7.27g of acrylate compound 9G and 180mL of tetrahydrofuran were mixed, and then the resulting mixture was heated at -60°C using 60 The polymer carrier was obtained by irradiating with Co-γ rays (dose rate: 15 kGy / h) for 4.5 h.
[0299] S2. Mix the 3D cage-shaped solid electrolyte composite microspheres with 350 mL of water, and then mix and shake them with the polymer carrier to make them fully swell to obtain a solid electrolyte hydrogel.
[0300] 3. Preparation of diaphragm
[0301] The solid electrolyte hydrogel was evenly coated on the upper and lower surfaces of a 36 μm thick PE base film (the upper and lower surfaces were coated with the same thickness), and dried to obtain a solid electrolyte separator with a thickness of 3.5 μm.
[0302] 4. Preparation of secondary batteries
[0303] K1. Lithium iron phosphate, carbon black and SBR are dry-mixed in a mass ratio of 72:18:10, and anhydrous ethanol is added to prepare a positive electrode slurry, which is coated on the positive electrode current collector aluminum foil, dried and sliced to obtain a positive electrode sheet.
[0304] K2. Mix the negative electrode active material (graphite), carbon black, SBR, CMC and anhydrous ethanol, wherein the mass ratio of the negative electrode active materials graphite, carbon black, SBR and CMC is 100:2:2:3, to obtain a negative electrode slurry; evenly coat the negative electrode slurry on the negative electrode collector copper foil, dry and slice it to obtain a negative electrode sheet.
[0305] K3. Stack the positive electrode sheet, the separator and the negative electrode sheet in sequence, and then wind them into a core to obtain an electrode assembly; put the wound electrode assembly into the battery shell, add electrolyte (LiPF6 electrolyte with a concentration of 1 mol / L, the solvents are EC and EMC, and the volume ratio of EC to EMC is 1:2), and after packaging, a secondary battery is obtained.
[0306] Example 10
[0307] 1. Preparation of 3D cage-shaped solid electrolyte composite microspheres
[0308] A) Add 2100g NMP as grinding medium into a sand mill, weigh 700g solid electrolyte Li 1.5 Al 0.5 Ti 1.5 (PO4)3 was added to a sand mill for sand grinding. The grinding balls used in the sand mill were zirconia balls (grinding ball diameter was 0.4 mm). The speed of the sand mill was set to 1800 r / min and the grinding time was 10 h. LATP slurry (D50 was 107 nm) was obtained by grinding. The slurry was then dried and stored to obtain ground LATP.
[0309] B) Weigh 5 g of the ground LATP obtained in step A) and perform LBL treatment, specifically: first immerse in a PEI solution (concentration of 5 mol / L, solvent is chloroform) at 45°C with magnetic stirring for 2 h, then immerse in a PEO solution (concentration of 5 mol / L, solvent is chloroform) at 45°C and 400 rpm with stirring for 2 h, which is the first alternating deposition. Repeat the above alternating deposition steps for a total of 3 alternating depositions, and then wash twice with deionized water to obtain modified LATP.
[0310] C) 3.1 g of brewer's yeast powder was weighed, washed with water and ethanol in sequence, and then dispersed in a HCl solution (with a concentration of 0.1 mol / L), and the pH was adjusted to 3 to obtain a yeast dispersion.
[0311] D) Under magnetic stirring, 5.8 g of the modified LATP obtained in step B) and 0.29 g of surfactant CMC were added to the yeast dispersion, and magnetic stirring was performed at 50° C. and 460 rpm for 3 h to obtain a mixed solution. Then, the mixed solution was transferred to a polytetrafluoroethylene-lined hydrothermal reactor and reacted at 130° C. for 4 h. Then, it was naturally cooled to room temperature, and the obtained precipitate was repeatedly washed with deionized water and ethanol, and dried in an oven at 85° C. to obtain a LATP-yeast-LATP complex.
[0312] E) placing the LATP-yeast-LATP complex obtained in step D) in a tubular heating furnace and continuously heating at 580° C. for 4 h under argon protection to obtain LATP@yeast carbon sphere@LATP composite microspheres, i.e., 3D cage-shaped solid electrolyte composite microspheres.
[0313] 2. Preparation of solid electrolyte hydrogel
[0314] S1, 14.3g of hydrophilic ionic monomer MAA, 8.17g of acrylate compound 9G and 150mL of dimethylformamide were mixed, and then the resulting mixture was heated at -78°C using 60 The polymer carrier was obtained by irradiating with Co-γ rays (dose rate: 10 kGy / h) for 3 h.
[0315] S2. Mix the 3D cage-shaped solid electrolyte composite microspheres with 400 mL of water, and then mix and shake them with the polymer carrier to make them fully swell to obtain a solid electrolyte hydrogel.
[0316] 3. Preparation of diaphragm
[0317] The solid electrolyte hydrogel was evenly coated on the upper and lower surfaces of a 30 μm thick PE base film (the upper and lower surfaces were coated with the same thickness), and dried to obtain a solid electrolyte separator with a thickness of 4.3 μm.
[0318] 4. Preparation of secondary batteries
[0319] K1. Lithium manganate, graphene and PVDF are dry-mixed in a mass ratio of 90:5:10, and NMP is added to prepare a positive electrode slurry, which is coated on a positive electrode current collector aluminum foil, dried and sliced to obtain a positive electrode sheet.
[0320] K2. Mix the negative electrode active material (graphite), graphene, PVDF, PVA and NMP, wherein the mass ratio of the negative electrode active materials graphite, graphene, PVDF and PVA is 100:1:1:4, to obtain a negative electrode slurry; evenly coat the negative electrode slurry on the negative electrode current collector copper foil, dry and slice it to obtain a negative electrode sheet.
[0321] K3. Stack the positive electrode sheet, the separator and the negative electrode sheet in sequence, and then wind them into a core to obtain an electrode assembly; put the wound electrode assembly into the battery shell, add electrolyte (LiPF6 electrolyte with a concentration of 1 mol / L, the solvents are EC and EMC, and the volume ratio of EC to EMC is 1:2), and after packaging, a secondary battery is obtained.
[0322] Comparative Example 1
[0323] The composite solid electrolyte membrane was prepared according to the method of Example 5, except that only the membrane layer and the Li 1.4 Al 0.4 Ti 1.6 The hydrogel layer prepared by (PO4)3 was prepared without introducing yeast, and the remaining steps and conditions were exactly the same as those in Example 5.
[0324] Comparative Example 2
[0325] The composite solid electrolyte membrane was prepared according to the method of Example 5, except that Li was coated with 30% glucose. 1.4 Al 0.4 Ti 1.6 (PO4)3, and then heated at 550°C for 6 hours for carbonization treatment. The remaining steps and conditions are exactly the same as those in Example 5. Specifically, the yeast powder in step C is replaced with 1.5g of glucose, and the remaining steps and conditions are exactly the same as those in Example 5.
[0326] Comparative Example 3
[0327] The composite solid electrolyte membrane was prepared according to the method of Example 5, except that the 3D cage-like solid electrolyte composite microspheres were mixed with NMP solvent to prepare a slurry of corresponding thickness and coated on the membrane without introducing gel. The remaining steps and conditions were exactly the same as those of Example 5.
[0328] Comparative Example 4
[0329] A composite solid electrolyte membrane was prepared according to the method of Example 5, except that it only contained a membrane layer and a hydrogel layer prepared from yeast microspheres, and no solid electrolyte was introduced. The remaining steps and conditions were exactly the same as those of Example 5.
[0330] Comparative Example 5
[0331] A composite solid electrolyte membrane was prepared according to the method of Example 5, except that only a membrane layer was included without introducing a coating layer, and the remaining steps and conditions were exactly the same as those of Example 5.
[0332] Performance Testing:
[0333] The following performance tests were performed on the composite diaphragms and lithium ion batteries of Examples 1 to 9 and Comparative Examples 1 to 5:
[0334] 1. The puncture strength, ionic conductivity, tensile strength and porosity of the composite membranes prepared in the above examples and comparative examples were tested according to the method in GB / T36363-2018; the 180° peeling force test of the composite membranes was performed with reference to GB / T2792 standard. The results are shown in Table 1.
[0335] Table 1: Test results of needle puncture strength, ionic conductivity, tensile strength and porosity
[0336]
[0337] 2. Battery room temperature cycle performance test method: At 25°C, charge the divided battery at 0.7C constant current and constant voltage to 4.48V, with a cut-off current of 0.05C, and then discharge it at 0.5C constant current to 3.0V. Repeat this cycle. After 500 cycles of charge and discharge, calculate the capacity retention rate at the 500th week, as shown in Table 2.
[0338] 3. High temperature (45°C) cycle test: 45°C, constant current 0.1C charging to 4.45V, CC-CV charging to a current less than 0.05C, 1C discharge to 3.0V, record the number of cycles before the battery capacity is less than 80%; see Table 2.
[0339] 4. Battery hot box performance test: Randomly select 6 lithium-ion battery samples, charge to 4.5V at 2A constant current and constant voltage, cut-off current 0.025A, and let stand for 60 minutes. Then put the fully charged soft-pack lithium battery in an oven, raise the temperature from room temperature to 130±2℃ at a rate of 5℃ / min, and keep it for 30 minutes before stopping. See Table 2.
[0340] Table 2: Electrical performance test results
[0341] High temperature cycle number -80% 500 cycles capacity retention 130℃ hot box pass rate Example 1 652 85% 5 / 6 Example 2 573 80% 6 / 6 Example 3 595 87% 4 / 6 Example 4 558 81% 5 / 6 Example 5 763 91% 6 / 6 Example 6 493 89% 5 / 6 Example 7 488 90% 5 / 6 Example 8 501 83% 4 / 6 Example 9 611 87% 6 / 6 Example 10 539 82% 5 / 6 Comparative Example 1 342 70% 3 / 6 Comparative Example 2 408 73% 2 / 6 Comparative Example 3 331 65% 3 / 6 Comparative Example 4 385 68% 2 / 6 Comparative Example 5 412 77% 3 / 6
[0342] It can be seen from the test results in Table 1 that the composite membrane of the present invention has a peeling force of more than 454 N / m, a needle puncture strength of more than 5.5 N, and an ionic conductivity of more than 3.12 × 10 -6 S / cm 2The above, the air permeability is above 203S / 100ml, and it is significantly better than the comparative example in terms of puncture strength, peeling force, air permeability, and ion conductivity, which further demonstrates the superiority of the semi-solid composite diaphragm of the present invention. By comparing Example 5 with Comparative Example 1, it can be proved that the addition of inorganic solid electrolyte can improve the ion conduction rate of the diaphragm, that is, improve the dynamic performance of the diaphragm; by comparing Example 5 with Comparative Example 2, it is proved that the introduction of 3D porous microspheres in the functional layer can reduce the reaction activity of lithium-ion batteries at high temperatures and improve the safety performance of the battery; by comparing Example 5 with Comparative Example 3, it is proved that the introduction of gel coating comprehensively improves the peeling force of the composite diaphragm; by comparing Example 5 with Comparative Example 4, it is proved that the addition of inorganic solid electrolyte particles can effectively improve the ionic conductivity of the diaphragm, enhance thermal stability, and help maintain battery performance and safety under high temperature conditions. The present invention mixes 3D porous carbon microspheres and inorganic solid electrolyte particles together in a gel manner to form a functional layer. This method can effectively improve the dynamic performance and safety of the battery while reducing the cost of layered coating.
[0343] It can be seen from the test results in Table 2 that after the separator of the present invention is used in the battery, the number of cycles before the battery capacity is less than 80% is more than 488, the capacity retention rate of 500 cycles is more than 80%, and the 130°C hot box pass rate is more than 4 / 6 (i.e., 67%), and the above performances are significantly better than those of Comparative Examples 1 to 5. It is proved that the present invention forms a functional layer on the separator by gelling 3D cage-like solid electrolyte composite microspheres, which can improve the electrochemical performance of the battery.
[0344] Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core ideas, including the best mode, and also enable any technician in the field to practice the present invention, including making and using any device or system, and implementing any combined method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, the present invention can also be improved and modified, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements similar to the literal expression of the claims, or if they include equivalent structural elements that are not substantially different from the literal expression of the claims, then these other embodiments should also be included in the scope of the claims.
Claims
1. A method for preparing 3D cage-shaped solid electrolyte composite microspheres, characterized in that: The following steps are involved: A) grinding the inorganic solid electrolyte to obtain a ground LATP; in, The inorganic solid electrolyte is a NASICON type solid electrolyte Li 1+x Al x Ti 2-x (PO4)3, 0≤x<1; B) subjecting the ground LATP obtained in step A) to LBL treatment to obtain modified LATP; in, In the LBL process, the cationic polymer is deposited first and then the anionic polymer; The cationic polymer is at least one of PLL, PDDA, PPy and PEI; The anionic polymer is at least one of PSS, PEO, PVDF and PAAS; C) dispersing yeast powder in acid solution to obtain yeast powder dispersion; D) mixing the yeast powder dispersion obtained in step C), the modified LATP obtained in step B) and a surfactant, and heating them for reaction to obtain a LATP-yeast-LATP complex; E) sintering the LATP-yeast-LATP complex obtained in step D) to obtain 3D cage-shaped solid electrolyte composite microspheres; There is no order restriction for step B) and step C).
2. The preparation method according to claim 1, characterized in that: In step C): The acid solution is HCl solution; The pH of the yeast powder dispersion is 2 to 3; In step D), the heating reaction temperature is 80-150° C. and the time is 3-7 hours.
3. The preparation method according to claim 1 or 2, characterized in that: In step D): The amount of yeast powder in the yeast powder dispersion is 20% to 50% of the mass of the modified LATP; The amount of the surfactant is 5% to 10% of the mass of the modified LATP; The surfactant is at least one of polyvinyl alcohol, sodium carboxymethyl cellulose and polyvinyl pyrrolidone.
4. The preparation method according to claim 1, characterized in that: In step E), the sintering treatment is carried out at a temperature of 500 to 700° C. and for a time of 2 to 6 hours.
5. A 3D cage-shaped solid electrolyte composite microsphere prepared by the preparation method according to any one of claims 1 to 4.
6. A method for preparing a solid electrolyte hydrogel, characterized in that: The following steps are involved: S1, mixing a hydrophilic ionic monomer, an acrylate compound and a solvent, and irradiating the mixture to obtain a polymer carrier; S2, mixing the mother ball, the solvent and the polymer carrier obtained in step S1 to obtain a solid electrolyte hydrogel; Wherein, the mother ball is the 3D cage-shaped solid electrolyte composite microsphere as described in claim 5.
7. The preparation method according to claim 6, characterized in that: In step S1: The hydrophilic ionic monomer is at least one of methacryloyloxyethyl trimethyl ammonium chloride, dimethyl diallyl ammonium chloride, acrylic acid, methacrylic acid, sodium p-styrene sulfonate and carboxylic acid betaine; The acrylate compound is at least one of diethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, non-ethylene glycol dimethacrylate and tetradecaethylene glycol dimethacrylate; The irradiation is carried out using 60 γ-ray irradiation of Co; The irradiation temperature is -80 to -50°C; The irradiation has a dose rate of 10 to 15 kGy / h and a duration of 1 to 5 hours.
8. A solid electrolyte hydrogel prepared by the preparation method according to any one of claims 6 to 7.
9. A method for preparing a diaphragm, characterized in that: The following steps are involved: coating the hydrogel on the surface of the basement membrane and drying it to obtain a separator; Wherein, the hydrogel is the solid electrolyte hydrogel according to claim 8.
10. A secondary battery, characterized in that: The diaphragm is a diaphragm prepared by the preparation method described in claim 9.
Citation Information
Cited By
Composite solid electrolyte diaphragm and preparation method thereof
CN121238157A
